Ageing in Developing Societies: Issues and Challenges. (September 2020) - Kohli, Neena; Chawla, Sarabjeet Kaur; Banerjee, Aditya; Srinete, Taru Parnika
Ageing has emerged as a major challenge in several developing societies. With falling fertility rates and increasing longevity as its main drivers, it is expected that by 2050, one in five people of the developing countries will be over 60 years of age. It is argued that on account of this, such societies would further encounter an increased demand for medical treatment, long-term care, financial and emotional support. They also are likely to face an enormous psychological burden. In the context of ageing, the article highlights some of the key issues and challenges encountered by the developing societies. Urbanisation, changing family structure and drifting intergenerational relationships are seen as factors that have led to a multitude of psychological problems like social isolation, loneliness, abuse and discrimination and depression in older adults. The article argues in support of health and other social protective measures and calls for the need to recognise the strengths of older adults with a view to integrate them into the mainstream.